Peritoneal dialysis in a crisis: Navigating a severe drought and pandemic in South Africa - Davidson, Bianca; Wearne, Nicola; Barday, Zibya; Manning, Kathryn; Majoni, Wilbert; Majoni, Wilbert; Divino-Filho, Jose Carolino; Webb, Christine; Geragotellis, Alexander; Patel, Sabiha; Papavarnavas, Nectarios; Jones, Erika (African Journal of Nephrology, 2025)
Background: A severe drought, followed by the COVID-19 pandemic, posed significant challenges to a South African peritoneal dialysis (PD) programme in Cape Town. The study reported here assessed the impact of these crises on peritonitis rates, bacterial organisms cultured, and patient and technique survival. Methods: This observational cohort study used data from a peritoneal dialysis registry from 2007 to 2022. The study population was categorized according to three periods: “Baseline” (2007–2014), “Drought” (2015–2019), and “COVID-19” (2020–2022). Baseline characteristics were recorded when PD began. Trends in peritonitis rates, organisms cultured and causes of technique failure were evaluated during each period. A drought-specific questionnaire explored water quality and source. Results: The cohort comprised 405 patients, representing 559 peritonitis events. There was no statistical difference overall in peritonitis rates, nor peritonitis-free survival at one year among the three periods. Despite Gram-positive organisms being the predominant species cultured, there was an increasing trend in Gram-negative peritonitis during the drought (24%, 46/195) compared to baseline (16%, 37/230) and COVID-19 (15%, 20/134) periods. Klebsiella pneumoniae was the predominant Gram-negative organism cultured overall. However, there was a rise in the proportion Escherichia coli cultured in the drought (17%) compared to the pre-drought (3%) periods. The proportion of Gram-negative catheter-related infections increased during the drought and COVID-19 periods (P = 0.001), with a predominance of Pseudomonas aeruginosa. Only 18% of patients boiled their water as instructed. Conclusion: The similarity in overall peritonitis rates for the three periods highlights the adaptability and sustainability of peritoneal dialysis as a treatment option, especially at a time of increasing environmental and public-health crises.